Comparative study on synthesis and properties of geopolymer fine aggregate from fly ashes. (20th February 2019) - Parvathy S, Sethu; Sharma, Anil Kumar; Anand, K.B.
Highlights: An attempt to utilise fly ash for the synthesis of artificial fine aggregate. Class C fly ash geopolymer fine aggregate (C-GFA) and class F fly ash geopolymer fine aggregate (F-GFA) were synthesised. Concrete utilizing C-GFA and F-GFA are satisfactory for structural applications. Abstract: The growing demand for river sand has caused rapid depletion of this natural resource, and hence it is necessary to find an alternative to replace natural river sand. In this aspect, few recent studies have shown the potential of using geopolymerization reactions to produce fine aggregates using class F fly ash (FFA) to replace natural sand. In this study, an attempt has been made to utilise waste coal ash (class C and class F fly ash) to produce artificial fine aggregate by using geopolymerization reactions. The physical properties of both class C fly ash geopolymer fine aggregate (C-GFA) and class F fly ash geopolymer fine aggregate (F-GFA) were compared with the properties of natural sand and manufactured sand (M-sand). The mortar specimen using C-GFA and F-GFA gained a strength of 83% and 75% of 28-day compressive strength of natural sand mortar cubes and 89.01% and 81% of M-sand mortar cubes respectively. The concrete specimen using C-GFA and F-GFA gained 80.24% and 75% of 28 days compressive strength of natural sand concrete cubes and 83.9% and 77% of M-sand concrete cubes respectively. This study shows that both C-GFA and F-GFA can be used to synthesize alternative fine aggregates to natural sand and M-sand that are used in construction activities.